A drainage study of the south-west portion of Upper Pampanga River Integrated Irrigation System - Irinco, Reinerio E.
The drainage problem of the south-west portion of the Upper Pampanga River Integrated Irrigation system (UPRIIS) in Nueva Ecija was evaluated both at the ground surface and sub-surface. A 9,456 hectare-area was chosen for this study based on the availability of daily measured groundwater table depths from March 15 to August 23, 1993. Surface drainage was analyzed by presenting a surface hydrologic water balance of the study area using average monthly rainfall and evaporation data. The surface drainage discharge capacity was relatively low (5.5 millimeters per day). Various components of groundwater flow which contributed to or caused the drainage problem were evaluated using appropriate water balance equations. The net lateral groundwater inflow was relatively very slow, sometimes zero flow exists. This slow groundwater movement was due to several factors, one of them is the presence of slow receding San Antonio Swamp. Although the swamp was outside the study area, it is localized at the confluence of Pampanga and Rio Chico Rivers which serve as the main drainage outlet of the study area.